IMPLEMENTATION METHODOLOGY MULTIPARADIGMATIC IN MODERN HIGHER EDUCATION - Chernuha, N.; Zhelanova, V. (Continuing Professional Education: Theory and Practice, 2019)
Represented article justifies the necessity and expediency of implementing poli-paradigm methodology in modern higher education. Definition analysis of major concepts was researched and explained, mainly “paradigm”, “educational paradigm.” Basing on comparative analysis essence of the phenomenon poli-paradigm as research methodology is a conceptual synthesis of several existing educational paradigms. As a result of comparative analysis of cognitive, personal, semantic paradigms in education (in other words their comparison and explanation of similarities, differences, advantages and disadvantages), it was proved that each characterized paradigm has its positives and limitations. It was found positive concepts of cognitive, personal, semantic paradigms of education. The examples of co-existence in the form of practically-oriented system of contextual studying were overviewed. Considering reflective education paradigm (mission, content, best practice and studying forms, the relationship between teacher and student, criteria, function). It is proved that reflexively oriented education paradigm has a number of obvious advantages: it is based on the realization of subjects of education of profession activity semantic features; aimed on creating of individual self- actualization (the individual as a “subject” of his life) allows you to develop such skills as grounded, reasoned, logically correct thinking; forms the ability to think independently and critically. The article confirms that the reflexive paradigm is a poli-paradigm synthesis of cognitive, personal, semantic paradigms, which are the basis of modern higher education.